Meropenem-vaborbactam: a critical positioning for the management of infections by Carbapenem-resistant Enterobacteriaceae. Issue 6 (3rd June 2022) - Mouktaroudi, Maria; Kotsaki, Antigone; Giamarellos-Bourboulis, Evangelos J.
ABSTRACT: Introduction: The review aims to review the positioning of meropenem-vaborbactam in clinical practice, taking into consideration the characteristics of other available drugs, namely ceftazidime-avibactam, plazomicin, and colistin. Areas covered: The search terms 'meropenem-vaborbactam' or RX7009 for the years 2006 until 2021 were used. Expert opinion: Coupling of meropenem with the cyclic boronate derivative varobactam enhances considerably the in vitro intrinsic activity of meropenem against isolates producing KPC ( Klebsiella pneumoniae- producing carbapenemase). The drug has linear elimination and the ratio of the area under the curve of the free drug to the minimum inhibitory concentration is the main pharmacodynamics variable determining bacterial clearance. Meropenem-vaborbactam is currently approved for the management of complicated urinary tract infections including acute pyelonephritis, complicated intraabdominal infections, and hospital-acquired pneumonia including ventilator-associated pneumonia.